Childhood adversity and behavioral health outcomes for youth: An investigation using state administrative data. (September 2015) - Lucenko, Barbara A.; Sharkova, Irina V.; Huber, Alice; Jemelka, Ron; Mancuso, David
Abstract: This study aimed to measure the relative contribution of adverse experiences to adolescent behavioral health problems using administrative data. Specifically, we sought to understand the predictive value of adverse experiences on the presence of mental health and substance abuse problems for youth receiving publicly funded social and health services. Medicaid claims and other service records were analyzed for 125, 123 youth age 12–17 and their biological parents. Measures from administrative records reflected presence of parental domestic violence, mental illness, substance abuse, criminal justice involvement, child abuse and/or neglect, homelessness, and death of a biological parent. Mental health and substance abuse status of adolescents were analyzed as functions of adverse experiences and other youth characteristics using logistic regression. In multivariate analyses, all predictors except parental domestic violence were statistically significant for substance abuse; parental death, parental mental illness, child abuse or neglect and homelessness were statistically significant for mental illness. Odds ratios for child abuse/neglect were particularly high in both models. The ability to identify risks during childhood using administrative data suggests the potential to target prevention and early intervention efforts for children with specific family risk factors who are at increased risk for developing behavioral health problems during adolescence. This study illustrates the utility of administrative data in understanding adverse experiences on children and the advantages and disadvantages of this approach.